Effective MR Molecular Imaging of Triple Negative Breast Cancer With an EDB-Fibronectin-Specific Contrast Agent at Reduced Doses - Ayat, Nadia R.; Vaidya, Amita; Yeung, Grace A.; Buford, Megan N.; Hall, Ryan C.; Qiao, Peter L.; Yu, Xin; Lu, Zheng-Rong (Frontiers in Oncology, 2019)
MR molecular imaging (MRMI) of abundant oncogenic biomarkers in tumor microenvironment has the potential to provide precision cancer imaging in high resolution. Extradomain-B fibronectin (EDB-FN) is an oncogenic extracellular matrix protein, highly expressed in aggressive triple negative breast cancer. A targeted macrocyclic gadolinium-based contrast agent (GBCA) ZD2-N3-Gd(HP-DO3A) (MT218), specific to EDB-FN, was developed for MRMI of aggressive breast cancer. The effectiveness of different doses of MT218 for MRMI was tested in MDA-MB-231 and Hs578T human triple negative breast cancer models. At clinical dose of 0.1 and subclinical dose of 0.04 mmol Gd/kg, MT218 rapidly bound to the extracellular matrix EDB-FN and produced robust tumor contrast enhancement in both the tumor models, as early as 1 min to 30 min post-injection. Substantial tumor enhancement was also observed in both the models with MT218 at doses as low as 0.02 mmol Gd/kg, which was significantly better than the clinical agent Gd(HP-DO3A) at 0.1 mmol Gd/kg. Little non-specific enhancement was observed in the normal tissues including liver, spleen, and brain for MT218 at all the tested doses, with renal clearance at 30 min. These results demonstrate that MRMI with reduced doses of MT218 is safe and effective for sensitive and specific imaging of aggressive breast cancers.